Crowdsourcing Digital Interior Design Platform as Green Business: A Business Model Canvas Analysis - Fathsyadira, Hastia; Lisan Suwarno, Henky (Lafadz Jaya Publisher, 2025)
The rise of digital technology has created new opportunities in the interior design industry, particularly through crowdsourcing-based platforms that support green business innovation. This study aims to analyze the business model of a digital interior design platform that connects clients and professional designers using a sustainable and collaborative approach. This research employed qualitative methods, including in-depth interviews, direct observations, and document analysis. The Business Model Canvas (BMC) framework was used to map and analyze the platform’s nine key components: customer segments, value propositions, channels, customer relationships, revenue streams, key resources, key activities, key partners, and cost structures. The analysis reveals that the platform targets eco-conscious clients and digitally savvy designers, offering value through accessible green design solutions, verified designer portfolios, and transparent transactions using features like ratings, reviews, and escrow payments. Social media and digital communities serve as the main communication and marketing channels. The study concludes that this crowdsourcing-based digital platform has strong potential to become a scalable and sustainable green business. By aligning environmental goals with digital innovation, the platform can meet the demands of modern consumers while promoting sustainable interior design practices. The BMC approach provides a practical tool for designing, evaluating, and improving the platform’s business model.